An Analysis of Oral and Written Feedback Given by English Teachers at SMP N 1 Enam Lingkung - Yolanda Efendi; Edi Trisno (Universitas Negeri Padang, 2021)
Feedback is the teacher's comments on the results of student work. The feedback can be written on the work or oral feedback, directly to the student concerned. There are many types of oral and written feedback and each type has a different function. This research aims to analyze the types of oral and written feedback of the English teachers in the teaching and learning process in SMP N 1Enam Lingkung. This research is descriptive research. The subjects of this research were 3 teachers selected by using the total sampling technique. The technique of data collection was classroom observation-video recording and written students’ assignments. The findings of this research are the most type of feedback used by the teachers in the teaching and learning process in SMP N 1 Enam Lingkung is evaluative feedback, with 82 feedback (53,94% of the total feedback). The second finding of the most type of written feedback used by teachers in students’ written assignments is direct feedback, with 80% of total feedback.